EVALUATION ON AGGREGATION RISK RATE FOR DEFUZZIFICATION IN FUZZY SETS - Kayalvizhi, S.; *, Gunasekar; *, Thenmozhi (IJRDO -Journal of Computer Science Engineering, 2016)
The main aim of the proposed method is to present that the defuzzification process usingmedian rule is not similar to the process that follows classical centroid rule. The classicalcentroid rule uses either triangular or trapezoid moments. The triangular or trapezoid is takenwith isosceles principle and defuzzification with such median principle is proved withreduced error tolerance.